2003
DOI: 10.1542/peds.112.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tube Defects: Knowledge and Preconceptional Prevention Practices in Minority Young Women

Abstract: Publicly funded clinics may be the only source of information on NTD prevention for many minority young women. Preliminary evidence suggests that a promotion program improves knowledge, and dispensing of multivitamins increases multivitamin use. However, clinicians in such programs need to reinforce daily adherence to multivitamins in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
4
32
3
Order By: Relevance
“…This showed significant increases four months after the intervention, with higher figures in those women who were not already taking a supplement. In the USA a trained health educator implemented a folic acid promotion programme at three clinics (Chacko et al) (58) . When a young woman indicated interest in taking a daily multivitamin, she was given a 3-month supply of multivitamin tablets.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…This showed significant increases four months after the intervention, with higher figures in those women who were not already taking a supplement. In the USA a trained health educator implemented a folic acid promotion programme at three clinics (Chacko et al) (58) . When a young woman indicated interest in taking a daily multivitamin, she was given a 3-month supply of multivitamin tablets.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Before the mandatory fortification of grains, the average consumption of folic acid was estimated to be 0.25mg/day and the fortification is estimated to add 0.1 mg/day, leaving many women of childbearing age under the recommended levels (Chacko et al, 2003). A study by Boushey and colleagues (2001) showed that 61% of women in childbearing age after fortification had intakes of folic acid below the recommended levels and those who achieved the guidelines were those who consumed supplements.…”
Section: Concernsmentioning
confidence: 99%
“…A follow-up survey of the program indicated that the daily intake of FA increased from 9% at the time of enrollment to 67% within 3 months into implementation of the program. 24 The other type of campaign takes on a more passive approach, such as a mass media campaign. This type of campaign can be effective in reaching sizable population in short time and is less costly.…”
Section: Strategies To Promote Folate Consumptionmentioning
confidence: 99%
“…Furthermore, efforts spent to look at predictors of suboptimal use of periconceptional FA identified that women, who When young (13-22 years of age) and low-income women were targeted in the FA promotion program in Huston, Texas, the daily multivitamin intake increased from 9% to 67%. 24 In addition, racial and ethnic disparities were found to influence FA consumption. Nonwhite and Hispanic women were the least likely to be aware of FA.…”
Section: Predictors Of Suboptimal Use Of Famentioning
confidence: 99%